Neighbourhood Planning: Reminiscence Towards Liveable Communities - Wahab, Bolanle; Kadiri, Waheed; Popoola, Ayobami; Adeleye, Bamiji; Dwamena, Robert A (UI Scholars Hub, 2024)
Urbanisation remains a topical discussion across the globe. According to the United Nations (2022), 68% of the world's population will be absorbed in urban areas by 2050. The envisaged rapid urbanisation in cities by 2050 is believed to be accompanied by various planning problems, which include accelerated climate change, urban slums, urban sprawl, poor sanitation, inadequate infrastructure, overcrowding, housing deficiency and transportation issues. To mitigate these planning problems, the role of effective urban planning cannot be overemphasised. Urban planning provides a pathway for overcoming the various challenges posed by urbanisation both in the present and in the future. Urban planning is the process of guiding and directing land use for physical development to ensure a high quality of life and well-being of residents through the improvement of infrastructures and facilities, optimal economic development, and efficient operations and services (Bibri, 2018). Also, urban planning plays a significant role in actualising the Sustainable Development Goals (SDGs), particularly SDG 11, which seeks to make human settlement inclusive and sustainable (RELX, 2024). This implies that with efficient urban planning, access to a high quality of life for all city dwellers can be ensured amidst the present and forecast rapid urbanisation that would be experienced by cities of the world. Planning as an ancient, multi-sectoral, and multidisciplinary discipline that is focused on the sustainable functioning and arrangement of space cannot be over-emphasized. As a discipline that is influenced by human habits, actions, policies and professional practices, planning (whether traditional or modern) is perceptual and suggests the role of humans in shaping settlements. Recognising this, the writing of Jagannath (2019) drawing on Clarence Perry neighbourhood ideology suggests that the need for planning is to be considered along a micro-level. The liveability of workplace and place of resident emerged from the view that NP was both a response to placelessness (along the micro planning unit of space) and response to the degenerated social and environmental conditions that emerged out of the industrial revolution. Neighbourhood planning according to Parker (2012) allows for a community based radical strategy to emerging spatial problem. The writer documented that neighbourhood planning provides a room for the merging of formal (government and agencies) ideas with the local or informal (community resident), such that a cooperation is able to achieve an inclusive neighbourhood defined solution to identified problems. Recognising this, Bradley (2018) wrote that where development policy may privilege the supposed objectivity of technocratic rationalism, participation brings other ways of knowing and different types of evidence and methods of evidence gathering to the understanding of place (p.2). He further wrote that participatory planning practice has been seen as a touchstone for the ability of technocratic knowledge to accommodate lay perspectives of lived space. The incorporation of place-based knowledge in development planning becomes integral to the epistemology through which abstract space is produced (p.24). In this special issue, the diverse nature of planning (with focus on urban and neighbourhoods) and environmental problems were addressed. The authors in the special issue provided a multi- and interdisciplinary approach to understanding planning and in fact neighbourhood planning as a tool to managing and achieving liveability amidst rapid urbanisation. In this special issue, from the twenty-one submissions and proposals, only thirteen were considered for publication. All the manuscript underwent a two expert blind review, plagiarism check and editorial reviews. The focus on the articles accepted for publication drew on local context to planning and responding wicked problems within local areas and the process of adopting immediate built-environment principles as captured in neighbourhood planning to managing these challenges that limits communal liveability. The importance of local context and ‘neighbourhood-ness’ of research draws on the position of Lee et al. (2022), that neighbourhood planning remains an under-utilised ideology, approach, and process of achieving community liveability. This issue, as presented in the section below, provides a critical eye and/or perception on the inter- and multidisciplinary prisms of neighbourhood planning as a sustainable approach to achieving liveable communities.